2014
DOI: 10.1016/j.autneu.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the role of the autonomic nervous system in the development and maintenance of Goldblatt hypertension in rats

Abstract: Despite extensive use of the renovascular/Goldblatt model of hypertension—2K-1C, and the use of renal denervation to treat drug resistant hypertensive patients, autonomic mechanisms that underpin the maintenance of this hypertension are important yet remain unclear. Our aim was to analyse cardiovascular autonomic function by power spectral density analysis of both arterial pressure and pulse interval measured continuously by radio telemetry for 6 weeks after renal artery clipping. Mean arterial pressure increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 45 publications
7
47
0
2
Order By: Relevance
“…For example, circulating ANG II levels are high, especially during phase I (first 4 weeks) of 2K1C renovascular hypertension, 9,10 and ANG II acting at AT1R within the NTS has been reported to attenuate baroreflex function. 12,14 Similar to the findings in the present study, Oliveira-Sales 7 demonstrated that during phase I of 2K1C hypertension there is an impairment of the baroreflex, and this may be related to the high levels of ANG II.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…For example, circulating ANG II levels are high, especially during phase I (first 4 weeks) of 2K1C renovascular hypertension, 9,10 and ANG II acting at AT1R within the NTS has been reported to attenuate baroreflex function. 12,14 Similar to the findings in the present study, Oliveira-Sales 7 demonstrated that during phase I of 2K1C hypertension there is an impairment of the baroreflex, and this may be related to the high levels of ANG II.…”
Section: Discussionsupporting
confidence: 88%
“…In phase II, both SNA and MAP are increased by volume retention, decreased sodium excretion, and an increase in ANG II sensitivity. 7,9,10 all of which might be not directly affected by the AT2R overexpression in the solitary-vagal complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations